A case study on productivity improvement in a display cases manufacturing industry. (22nd September 2020) - Jayachitra, R.; Parthasarathy, S.
At the present stages of economic development, one of the main components of successful industrial organisation is productivity planning. Increase in productivity either reduces the production cost or increases the output. Productivity growth is becoming more important against a backdrop of market relations, because it allows the industry to stay competitive in the market and strengthen the social component in the development of society. The purpose of this work is to implement lean manufacturing concepts in display case manufacturing industry and to improve its productivity. At present, the industry is facing problem of low productivity due to increase in lead time of manufacturing display cases, wastage in the manufacturing process, under utilisation of workspace and under utilisation of human resources etc. Due to low productivity, the industry is unable to meet the demand. Hence, the objective is set to improve productivity of the industry to the possible extent. The objective is accomplished by implementing 5S, effective utilisation of workspace, effective utilisation of human resources, change in the plant layout and reducing the non productive time.